Educazione e natura (FrancoAngeli, 2022)
Starting from the binomial education/nature, the book explores issues relating to the broad field of outdoor education, in a choral analysis that aims to restore the plurality of approaches, choices and possible nuances. The text, in fact, develops the reflection in different directions through perspectives that come from different disciplinary fields (anthropological, architectural, biological, geographical, naturalistic, pedagogical and didactic, psychological, ethical...), but all aimed at overcoming reductionist visions that risk to reduce the debate on the subject and not guarantee the possibility of impact and change. What emerges is a legitimate and credible multi-faceted approach which, rather than synthesising and reducing, opens up further fields of research in a public debate that can no longer be delayed. This book is the result of in-depth work carried out as part of the inter-university specialisation course "Education and Nature" - conducted jointly by the Departments of Human Sciences for Education "Riccardo Massa" of the University of Milan Bicocca, of Human and Social Sciences of the University of Valle d'Aosta, of Educational Sciences "Giovanni Maria Bertin" of the University of Bologna and of Humanities, Social Sciences and Cultural Industries of the University of Parma (and previously by the Department of Education and Human Sciences of the University of Modena and Reggio Emilia) - and includes contributions by: Francesca Agostini, Francesca Antonacci, Maja Antonietti, Antonella Bachiorri, Giuseppe Barbiero, Fabrizio Bertolino, Cristina Birbes, Bettina Bolten, Mirella D'Ascenzo, Roberto Farné, Monica Guerra, Elena Mignosi, Luigina Mortari, Anna Perazzone, Andrea Pintus, Valentina Porcellana, Michela Schenetti, Enrico Squarcina, Mauro Van Aken, Beate Weyland.